Reasons for Inconsistent Condom Use Found as Answers to a Multiple Response Question: A National Survey of Iranian Adults, 2013 - Mirzaee, Moghaddameh (J Res Health Sci, 2017)
Background: The use of condoms is important for preventing Sexually Transmitted Infections (STIs). However, the prevalence of condom use is not satisfactory. The aim of this study was to assess the reasons for inconsistent condom use in Iranian adults. Study design: Cross-sectional study. Methods: Data were gathered through multi-stage sampling. Participants were enrolled from 13 provinces in Iran aged between 19 and 29 years. They had ever-extramarital sex and did not use condoms regularly in their sexual contacts, asked the reasons for inconsistent condom use. Results: We had 3,246 adults, from which 635 (19.5%) had ever-extramarital sex. Among them, 495 (77.96%) did not use condoms with regularity. The reason frequently chosen for inconsistent condom use was ‘that it is not accessible’ (49.3%). The differences between the categories of some variables, according to the choice of reasons for inconsistent condom use, were significant (P<0.05): age, gender, knowledge of HIV, attitude towards HIV, knowing infected HIV person and alcohol or stimulant(s) used before sexual contact. According to multivariate multilevel logistic, the effect of gender was significant on most of reasons for inconsistent condom use (P<0.05). Conclusions: Most of the reasons that were selected for inconsistent condom use were inaccessibility and not knowing that its use is essential. Hence, it is important to improve the knowledge of adults regarding STI/HIV and extend the locations of condom distribution. We should try to promote the culture of condom use as a routine.